Municipal Liability for Police Misconduct Under 42 U.S.C. § 1983 After City of Oklahoma City v. Tuttle - Solomon Oliver Jr. (Washington University Law Quarterly, 1986)
During its 1984 Term, City of Oklahoma City v. Tuttle presented the Supreme Court with two issues concerning what constitutes policy in the context of a police misconduct case: (1) whether proof of a single unusually excessive act of force by one officer, standing alone, could be sufficient to establish a policy of inadequate training by the city, and (2) whether a single act of police misconduct could be the basis of municipal liability if a policy of inadequate training were established through evidence independent of the act itself. This Article analyzes the Court's recent decision in Tuttle and its potential impact on police misconduct litigation. The primary focus of this Article is on the issue the Court left undecided in Tuttle. Lower court treatment of inadequate training as a basis of recovery has been confused and unclear due to a failure to distinguish "policy" from "custom." This Article concludes that inadequate training should be viewed as "policy" and thus it is unnecessary to establish a pattern of violations as with "custom"; recovery may be had even upon proof of just one violation. This Article further concludes that none of the issues Justice Rehnquist raised should be resolved in a manner that denies or limits inadequate training as a theory of recovery. The clarification of the nature of inadequate training as a theory of recovery against a municipality for police misconduct will also serve to resolve the issue as to whether the failure to act may be viewed as policy in other contexts as well.
Keywords: Municipal corporations; Government liability; Civil rights; Police